American Frontline Healthcare Personnel's Access to and Use of Personal Protective Equipment Early in the COVID-19 Pandemic. Issue 11 (7th November 2021) - Rich-Edwards, Janet W.; Ding, Ming; Rocheleau, Carissa M.; Boiano, James M.; Kang, Jae H.; Becene, Iris; Nguyen, Long H.; Chan, Andrew T.; Hart, Jaime E.; Chavarro, Jorge E.; Lawson, Christina C.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: To quantify adequacy of personal protective equipment (PPE) for U.S. healthcare personnel (HCP) at the outset of the COVID-19 pandemic and its association with infection risk. Methods: March–May 2020 survey of the national Nurses' Health Studies and the Growing Up Today study regarding self-reported PPE access, use, and reuse. COVID-19 endpoints included SARS-CoV-2 tests and COVID-19 status predicted from symptoms. Results: Nearly 22% of 22, 232 frontline HCP interacting with COVID-19 patients reported sometimes or always lacking PPE. Fifty percent of HCP reported not needing respirators, including 13% of those working in COVID-19 units. Lack of PPE was cross-sectionally associated with two-fold or greater odds of COVID-19 among those who interacted with infected patients. Conclusion: These data show the need to improve the U.S. infection prevention culture of safety when confronting a novel pathogen.